THE IMPLEMENTATIONS OF KBK (COMPETENCY-BASED), KTSP (SCHOOL- BASED), AND K-13 CURRICULA; A COMPARATIVE ANALYSIS - Riris Sugianto; Aini Husnida Wulandari; Lalu Isnaeni Rahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The curriculum, a governmental initiative within the educational sphere, evolves in response to societal shifts and advancements in science and technology. This research employs qualitative methods to generate descriptive data on the educational curriculum as a visible social construct. This social construct is then scrutinized through the lens of public policy theory. The study concludes that the curriculum, as a political measure by the Indonesian government in education, logically follows societal evolution and scientific progress. Over the period from 1999 to 2013, there have been three iterations of the curriculum: the Competency-Based Curriculum (KBK), the Education Unit Level Curriculum (KTSP), and the 2013 Curriculum (K-13). Each curriculum emphasizes distinct focal points and objectives. The government's revisions to the curriculum, guided by public policy theory, aim to meet the evolving needs and interests of the community. This ensures that the curriculum remains responsive to the changing social dynamics and advancements in science and technology within Indonesia and globally.